PERLINDUNGAN TERHADAP HAK RESTITUSI KORBAN TINDAK PIDANA PENIPUAN TERKAIT DISPARITAS PENERAPAN RESTITUSI OLEH PENGADILAN - Rachmat Harijanto; Timbo Mangaranap Sirait (The Juris, 2023)
There are implementation problems due to the regulation of victim restitution, but some weaknesses can cause implementation problems. The purpose of this research is to examine money laundering restitution agreements and measures to protect and fulfill victims' restitution requests in Decision 1/PID.SUS/2023/PT.BDG. This research was conducted using the normative legal method. This research uses a legal approach based on relevant laws and regulations, a conceptual approach based on recognized legal theories and concepts, and a case study approach on cases relevant to this research. From the study results, it is concluded that there is ambiguity in the law's reimbursement regime which raises doubts about its application among law enforcement officials. This may result in victims failing or claims for damages being rejected. Moreover, in Decision No. 1/PID.SUS/2023/PT.BDG, the role of the judge and prosecutor is very important so that the defendant is willing to pay compensation. Even if the victim is reluctant to ask for restitution, the judge or prosecutor can ask the defendant to pay the victim.